Educational model in the level of knowledge of nursing mothers and recovery at risk of malnutrition - Ramírez-Chumbe, Isabel (2019)
This study was conducted to determine the effectiveness of the food educational model in the level of knowledge of mothers and in recovery of infants from 6 to 11 months at risk of malnutrition Health Post Husares del Perú. It is a quasi-experimental, analytical, prospective and longitudinal type, whose sample consisted of 15 mothers and 15 children between 6 to 11 months at risk of malnutrition. Data were collected through interview techniques, anthropometry and demonstration. The questionnaire was used to measure the level of knowledge of mothers on food and nutrition. The anthropometric evaluation enabled us to observe the loss, gain and recovery of weight and the program of food educational model. The results were: The level of knowledge before the intervention was low (60%) and after high (73.3%) and in the recovery of risk of malnutrition before the intervention the average weight was 7.87 kg and after the intervention at 90 days, 93.33% (14) w8-9 Kg. when the X2 test (chi square) was applied to the variable level of knowledge was XC2 = 18.4> XT2. And for therisk of malnutrition T Student, tc = 4.63 at 90 days highly signicant. Therefore H1 = X2> X1, the food educational model produces signicant effect on the level of knowledge of mothers and in recovery of infants from six to eleven months at risk of malnutrition from Health Post Húsares del Peru, Pucallpa 2012.